ANALISIS PERAN KOMUNIKASI PUBLIK DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KELURAHAN DAMAR SARI KOTA TEBING TINGGI - Sara Agustin Simamora; Artha Tobing; Dimpos Manalu (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the role of public communication in improving the quality of public services in Damar Sari Village, Tebing Tinggi City. Public communication is a crucial aspect of public service delivery because it influences information delivery, transparency, and the relationship between the government and the public. Effective public services require clear, open, and responsive communication so that the public can understand service procedures and effectively express their needs and complaints.The research method used in this study was a qualitative method with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation of village officials and the community as service users. Data analysis was conducted by collecting, reducing, presenting data, and drawing conclusions from the research results obtained in the field.The research results indicate that public communication in Damar Sari Village plays a crucial role in improving the quality of public services. This is evident in the delivery of service information through various media, direct interaction between village officials and the public, and efforts to ensure transparency in the service process. However, several obstacles remain, such as limited communication facilities, inadequate use of digital media, and a lack of understanding of service procedures among the public.Based on these research results, it can be concluded that effective public communication can support the improvement of the quality of public services in Damar Sari Village. Therefore, improvements in the use of communication media, the provision of clearer and more accessible information, and improvements in the communication skills of officials are needed to optimize public services.